PENETAPAN KADAR ALKALOID TOTAL PADA EKSTRAK N-HEKSAN DAN ETANOL BIJI KETUMBAR (Coriandrum sativum) MENGGUNAKAN SPEKTROFOTOMETER UV-Vis - setyaningrum, lindawati; Susanti, Dhina Ayu (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2022)
Coriander (Coriandrum sativum) is one of the medicinal plants which is known to contain secondary metabolites such as flavonoids, tannins, terpenoids, saponins, steroids, and alkaloids. Alkaloids have therapeutic effects as antimalarials and cancer. Research in determining the alkaloids in coriander was carried out by separating the alkaloids from other substances using the soxhlet method extraction with two solvents ethanol and n-hexane. The total alkaloid content is determined using a UV-VIS spectrophotometer at wavelength 351,5 nm. The reaction of alkaloids with Bromocresol green (BCG) is obtained to form a yellow product. The use of berberine standard was obtained the total alkaloid content of ethanol and n-hexane extract in coriander seed (Coriandrum sativum) were 0.524% and 0.583% respectively, and the ratio of total alkaloid content of ethanol extract was smaller than that of n-hexane extract.